Analisis Kreativitas Guru Dalam Meningkatkan Kemampuan Membaca Permulaan Anak Kelompok B2 Di Tk Mutiara Hati - Nurul Iqamah; Gunawan Gunawan; Fahruddin Fahruddin; Ni Luh Putu Nina Sriwarthini (Indonesian Journal of Elementary and Childhood Education, 2023)
This research was motivated by the lack of initial reading skills of children in the B2 group at school. This research aims to analyze teacher creativity in improving the beginning reading skills of group B2 children at Mutiara Hati Kindergarten and this research also analyzes the inhibiting and supporting factors for teachers in improving the beginning reading abilities of group B2 children at Mutiara Hati Kindergarten. This research uses qualitative research with descriptive methods. Data collection techniques use observation, interviews and documentation. The data sources in this research were 3 teachers and 10 children from group B2. Based on the research results, it shows that teacher creativity in improving the beginning reading skills of children in group B2 with teacher achievement is 80% -88% which shows that teachers at Mutiara Hati Kindergarten have very good creativity with the teacher's efforts to create fun activities, teachers use varied learning methods and Teachers can carry out activities that attract children's attention. These efforts and methods can improve the initial reading ability of children in group B2, indicated by the child's development having developed very well and developing in line with expectations. The inhibiting factors for teacher creativity in improving the initial reading skills of B2 group children at Mutiara Hati Kindergarten are children's lack of focus, diverse children's characteristics, lack of support from parents. The supporting factors for teacher creativity in improving the initial reading skills of children in the B2 group at Mutiara Hati Kindergarten are teacher ability and school support.